The Relationship Between Self-Control and Self-Efficacy Among Patients With Substance Use Disorders: Resilience and Self-Esteem as Mediators - Yang, Chunyu; Zhou, You; Cao, Qilong; Xia, Mengfan; An, Jing (Frontiers in Psychiatry, 2019)
Abstract Background: While substance use disorder is one of the overarching health and social issues, that might seriously disrupt individuals’ self-control and self-efficacy, most previous studies have been conducted among university students or other groups, and little is known about how the underlying mechanisms between self-control and self-efficacy might impact patients with Substance Use Disorders. Objectives: The purpose of this study is to investigate how resilience and self-esteem mediate the relationships between self-control and self-efficacy among patients with Substance Use Disorders. Methods: We conducted a cross-sectional study of 298 patients with substance use disorder from Shifosi rehab in China. DSM-5 based diagnostic questionnaires were used to collect demographic information and assess addiction severity. The Dual-Modes of Self-Control Scale (DMSC-S) was implemented to measure self-control, while self-esteem was measured using the Self-esteem Scale (SES). The Connor-Davidson Resilience Scale (CD-RISC) was used to measure resilience, and self-efficacy was measured by the regulatory emotional self-efficacy Scale (RESE). Results: The correlations between all the dimensions and total scores on the self-control, resilience, self-esteem, and self-efficacy were significantly positive (p<0.01), indicating that they could predict patients’ self-efficacy. Bootstrap testing indicated that resilience and self-esteem fully mediated the relationship between self-control and self-efficacy, relationships between self-control and self-esteem were partially mediated by resilience, and resilience partially mediated the relationship between self-esteem and self-efficacy. Finally, the multiple-group analysis indicated that the relationships among self-control, resilience, self-esteem and self-efficiency did not differ with respect to gender. Conclusions: The path from self-control through resilience and self-esteem and on to self-efficacy is significant among patients with substance use disorders, suggesting that increasing self-control, resilience, and self-esteem can improve self-efficacy among patients with Substance Use Disorders.